Concept for Automated Fuse and Relay Assembly in the Field of Cable Harness Manufacturing - Heisler, Paul; Sand, Christian; Hefner, Florian; Süß-Wolf, Robert; Franke, Jörg (RWTH Aachen 2017 – 7. WGP-Jahreskongress, 2017)

Design of process parameters for the manufacturing of wrapped connections with single solid round wires using the explicit finite element analysis - Hefner, Florian; Praß, Julian; Kirchner, Philipp; Franke, Jörg (Procedia CIRP, 2020)
Keywords: process simulation; wrapped connections; explicit finite element analysis

Distributed Camera Architecture for Seamless Detection and Tracking of Dynamic Obstacles - Scholz, Michael; Steinkamp, Jan; Zwingel, Maximilian; Hefner, Florian; Franke, Jörg (Procedia CIRP Volume 91, 2020)
Tracking of dynamic objects is a key element especially for in-door logistic solutions but also for e.g. manufacturing plants and warehouses. This paper is dealing with a tracking approach which is based on multiple cameras that are permanently mounted on the ceiling. In comparison to currently applied methods of detecting and tracking dynamic objects in the field of AGVs this approach is innovative. This is due to the shift in the capture of tracking data to ceiling cameras exclusively, for the reason of gaining a holistic overview of the complete tracking area. The application case discussed in this paper is for AGVs in the frame of a research project. However, this approach can be applied for different use cases which require a pursuit and tracking of dynamic objects that is based on multiple cameras.
Keywords: logistics; Flexible manufacturing system (FMS); Distributed design

High-precision assembly of electronic devices with lightweight robots through sensor-guided insertion - Metzner, Maximilian; Leurer, Sebastian; Handwerker, Andreas; Karlidag, Engin; Blank, Andreas; Hefner, Florian; Franke, Jörg (Procedia CIRP, 2020)
Through-hole devices still play an important role in power electronics production. Due to a high number of variants in this field, an automated placement by special machines is often not economically feasible. The resulting manual process is characterized by monotony, ergonomic strain and high labor cost. As a result, a partial automation, using lightweight robots in hybrid assembly system, yields high potential. The lower stiffness and resulting accuracy deficiency of lightweight robots compared to common industrial robots, combined with the precision requirements and inherent fragility of the devices, prohibits the deployment of such systems. In this contribution, a scalable setup and strategies for visual and force-torque guided tactile insertion of such devices is presented and evaluated. A library, based on a system for the offline-programming of such tasks, is used to decrease implementation efforts. A performance evaluation of the system on printed circuit boards with multiple different devices is conducted.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Electronics production; Lightweight robots; Offline programming; Peg in Hole

Innovative signal and power connection solutions for alternative powertrain concepts - Fröhlig, Simon; Piechulek, Niklas; Friedlein, Matthias; Süß-Wolf, Robert; Schmidt, Lorenz; Kuhn, Marlene; Wang, Li; Hefner, Florian; Heisler, Paul; Fröhlich, Jan; Meiners, Moritz; Franke, Jörg (2020 10th International Electric Drives Production Conference (EDPC), 2020)
Since the automotive wiring harness interconnects all electrical components in a vehicle, it also must adapt to all componential, mechanical, and electrical architecture changes. For this reason, almost all trends that affect the vehicle in general also affect the wiring system. This paper describes the current situation, analyses the most important trends in the automotive industry, and discusses their effects on the wiring system. In particular, the focus is on the current megatrend of electromobility and the associated electrification of the powertrain. In addition to the integration of autonomous driving functions and Car-To-X- Communication, the electrification adds new requirements and tasks for the wire harness. In this context, a holistic approach is taken to combine various fields of research such as automation solutions, computer-aided technologies, functional integration, as well as reliability models to offer a solution for the challenges caused by current automotive trends.<br
Keywords: electromobility; wiring harness; vehicle electrical system; signal and power connection; alternative powertrain

Optimizing the wiring sequence based on a Constraint Satisfaction Problem for robot-based manufacturing of solderless wrapped connections - Hefner, Florian; Schmidbauer, Simon; Franke, Jörg (Procedia CIRP, 2022)
The manufacturing of solderless wrapped connections in traceable and reproducible high quality requires an automated manufacturing process. However, one key challenge for robot-based wiring is the definition of wiring sequence, as the proximity of the array-oriented wrapposts exacerbates tool accessibility. In this research, we optimize the wiring sequence by treating it as a constraint satisfaction problem, whereby a solution is indispensable, even if the constraints are not fulfilled. Experiments on a pilot plant for robot-based manufacturing of wrapped connections show that the percentage of automatically wired connections can be significantly increased with the developed approach.
CRIS-Team Scopus Importer:2022-12-09
Keywords: automation; Constraint Satisfaction Problem; control cabinet; lightweight robot; solderless wrapped connection; sorting algorithm; wiring

Pose error correction of a robot end-effector using a 3D visual sensor for control cabinet wiring - Hefner, Florian; Schmidbauer, Simon; Franke, Jörg (Procedia CIRP, 2020)
The wiring of control cabinets in small and medium-sized enterprises is a mostly manually performed process and very time-consuming. Thus, an automated approach for wiring control cabinets is necessary. The proposed solution is based on an ECAD model and performed by a lightweight robot. Before the wire insertion, the tip pose of the gripped wire end and the component port pose are detected by processing 3D sensor data. The sensor is able to detect wire ends with arbitrary cross-section geometries and arbitrary component port shapes. The results prove the functionality of correcting the pose of the robot end-effector with respect to a component port using a 3D sensor.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Automated control cabinet wiring; Flexible manufacturing; Pose correction; Position-based visual servoing; Robot-based automation

Potenziale zur Produktionsautomatisierung. Systematische Vorgehensweise zur Identifikation von Automatisierungsprojekten - Herbert, Meike; Selmaier, Andreas; Hefner, Florian; Franke, Jörg (wt Werkstattstechnik - Online, 2020)
Unternehmen der produzierenden Industrie, insbesondere der deutsche Mittelstand, sind bei der digitalen Transformation mit vielen Herausforderungen konfrontiert, beginnend mit der Analyse und Identifikation geeigneter Automatisierungsprojekte. In dem Beitrag wird eine ganzheitliche Vorgehensweise vorgestellt, um Potenziale für eine Automatisierung in Produktion und Logistik zu erkennen und konkrete Projekte zu definieren.<br
Keywords: Automatisierung; Industrie 4.0; Strategie

Robot-based automated production of wrapped connections with single solid round wires - Hefner, Florian; Herbert, Meike; Sjarov, Martin; Süß-Wolf, Robert; Franke, Jörg (Production at the leading edge of technology, 2019)
The solderless wrapping process is an electrical connection technology. It is mainly used in applications which require high reliability, such as the aerospace industry. A single solid conductor is wrapped around a connecting terminal. The process is currently being realized manually and the worker's qualification highly determines the overall process quality and efficiency. The challenges of this specific task include the handling of the flexible wire, the production process of standard-conforming wrapped connections and the required positioning accuracy of the tool relative to the wrappost. An automation of the production process is essential to meet the increasing quality and efficiency requirements of modern production environments, however, available solutions still highly rely on the operator and therefore lack the aspired automation degree. To enable the automated production of wrapped connections, a lightweight robot is equipped with several components. In this paper, the design of the whole system, including the newly developed robotic end-effector, is presented. The main components are two wrapping tools, each driven by an electric motor and attached to an electric slide. The device can be moved onto the wrappost extending the electric slide. A wire feeder realizes the conveying movement of the wire. Moreover, an optical sensor is used to determine the wrappost's position and orientation. The newly developed system enables the automated production of wrapped connections conforming to standards.<br
Keywords: wrapped connections; robot-based automation; flexible manufacturing

Vision-based adjusting of a digital model to real-world conditions for wire insertion tasks - Hefner, Florian; Schmidbauer, Simon; Franke, Jörg (Procedia CIRP, 2020)
In small and medium-sized enterprises, the wiring of control cabinets is a very time-consuming process as it is mostly performed manually. Thus, a novel automated approach for wiring control cabinets with batch size 1 is provided. The task is executed by a lightweight robot and based on an ECAD model of a wired cabinet. Therefore, a method is described to export digital data from ECAD and adjust the digital information to real-world conditions. To detect the approximate real-world poses of the components, a 2D image from a stationary visual sensor is used for CAD-based template matching by normalized cross-correlation. A high accurate visual 3D sensor that is mounted on the robot end-effector is moved to the approximate poses of the component ports to measure the exact poses. The results prove the functionality of the developed method, which allows to position the robotic end-effector based on ECAD data, which is the prerequisite to measure the component port with high accuracy using the 3D sensor.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Automated control cabinet wiring; ECAD; Flexible manufacturing; OpenCV; Robot-based automation; Template matching